Corporate Social Responsibility In Islamic Business: Case Study Of Indonesia Company - Arsetyo, Yulio Iqbal Cahyo (Universitas Islam Indonesia, 2021)
It is widely acknowledged that Corporate Social Responsibility (CSR) has become socially “mandatory” for company to partake in the development of their community. Furthermore, CSR fills the blank space where the government cannot reach or has limited access. This paper will be addressing two issues: (a) CSR concept in accordance with Islamic Value; and (b) How the Indonesian Government regulates the application of Islamic CSR Model in the country. This research aims to analyze the concept of Zakat as a CSR model under the Islamic Business Law, with the objective to compare Zakat and the conventional CSR. This research is conducted in Normative-Juridical method which establishes that Islamic CSR means more than just “helping the humanity and the environment”, but also as a “Heavenly duty”, as opposed to Western business system in which CSR serves as the company’s tool to protect its interest and public image leverage.Keywords: Corporate Social Responsibility; Islamic Business Model; Law; ZakatTanggung Jawab Sosial Perusahaan Dalam Bisnis Islam: Studi Kasus Perusahaan Di IndonesiaAbstrakDiakui secara luas bahwa Tanggung Jawab Sosial Perusahaan atau Corporate Social Responsibility (CSR) telah menjadi “hal wajib” secara sosial bagi perusahaan untuk mengambil bagian dalam pengembangan komunitas mereka. Selanjutnya, CSR mengisi ruang kosong yang tidak dapat dijangkau atau dibatasi oleh pemerintah. Tulisan ini akan membahas dua hal: (a) konsep CSR sesuai dengan Nilai Islam; dan (b) Bagaimana Pemerintah Indonesia mengatur penerapan Model CSR Syariah di Tanah Air. Penelitian ini bertujuan untuk menganalisis konsep Zakat sebagai model CSR menurut Hukum Bisnis Islam, dengan tujuan untuk membandingkan Zakat dan CSR konvensional. Penelitian ini dilakukan dengan metode Normatif-Yuridis yang menetapkan bahwa CSR Islam berarti lebih dari sekedar “membantu kemanusiaan dan lingkungan”, tetapi juga sebagai “tugas Surgawi”, berbeda dengan sistem bisnis Barat di mana CSR berfungsi sebagai alat perusahaan. untuk melindungi kepentingan dan pengaruh citra publiknya.Kata kunci: Tanggung jawab sosial perusahaan; Model Bisnis Islami; Hukum; zakat